Identifikasi Jamur Kontaminan pada Petis Udang yang Dijual di Pasar Pagi Tegal - Naqsyabandi S; Suparyati Suparyati; Gustina N (Jurnal Kebidanan Harapan Ibu Pekalongan, 2022)
Shrimp paste is the result of processing broth or shrimp juice which is blackish brown in color and has a distinctive aroma. Usually the raw material for making shrimp paste is a whole shrimp head, ground and given enough water and then squeezed. Shrimp paste that is stored for too long or open state in the storage allows shrimp paste to be contaminated by bacteria and fungi such as Rhizopus sp, Mucor sp, Aspergillus sp and Penicillium sp. The purpose of this study was to determine whether there was fungal contamination in shrimp paste sold at the Pasar Pagi Tegal. The research method used is descriptive research, which is describes the phenomenon of the object under study in the narrative form. Samples were obtained by taking 12 samples of shrimp paste taken from 12 shrimp paste traders in Pasar Pagi Tegal. The fungus was identified by culturing on Sabouraud Glucose Agar (SGA) media, incubated for 3-7 days at 37ºC and then observed macroscopically and microscopically. The results showed that based on macroscopic and microscopic examinations, shrimp paste sold at Pasar Pagi Tegal was 34% contaminated with Aspergillus sp, 33% contaminated with Penicillium sp and Aspergillus sp, 17% contaminated with Penicillium sp, 8% contaminated with Rhizopus sp and Aspergillus sp, and 8% contaminated with Rhizopus sp